Efikasi Diri, Kematangan Emosi dan Problem Focus Coping - Prasetyo, Yanto (Persona:Jurnal Psikologi Indonesia, 2016)
The study is aimed to find out the correlation between self efficacy and emotional maturity with problem focused coping.. Data collection is performed by means of three scales namely problem focused coping scale, self efficacy scale, and emotional maturity scale. The test of major hypothesis is performed by means of multiple regression analysis and shows that there is a significant correlation between self efficacy and emotional maturity with problem focused coping by F reg = 29.584; p = .00 (p< .01). The test result of first minor hypothesis shows that there is a positive and significant correlation between self efficacy with problem focused coping. The higher the self efficacy of employee is, the better his/her work performance is and vice versa that is showed by r score = .309 ; p = .02 (p< .01). The contribution of self efficacy toward the problem focused coping is 22.135%. The test result of second minor hypothesis shows that there is a very positive and significant correlation between emotional maturity with problem focused coping, the higher score of emotional maturity achieved by the employee is the better his/her problem focused coping is. It is showed by r x2y-1 score = .396 ; p = .003 (p< .01). The contribution of emotional maturity to problem focused coping is 30.614%.Keywords: Self Efficacy, Emotional Maturity, Problem Focused Coping.